1992
DOI: 10.1016/0147-1767(92)90008-i
|View full text |Cite
|
Sign up to set email alerts
|

Personal investment in Japan and the U.S.A.: A study of worker motivation

Abstract: The Inventory of Personal Investment (IPI) was administered to 522 Japanese and 746 American workers to compare their work motivation and self-concepts. Eleven subscales were formed based on the IPI model and were found through factor analysis to be appropriate for the samples in both countries. Discriminant analyses of scale scores by subjects' nationality, gender, occupational strata, and age are reported. Findings included: (1) Japanese and American workers sampled emphasized different aspects of meaning as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Misra et al (1990) found greater linkage between work and family concerns in India than in Canada. Schwalb et al (1992) found that Japanese employees reported being motivated by the task itself, self-improvement, and financial reward, in contrast with a greater US emphasis upon affiliation, social concern, and recognition. Holt & Keats (1992) compared Anglo, Chinese, Lebanese, and Aboriginal Australians.…”
Section: Work Motivationmentioning
confidence: 88%
“…Misra et al (1990) found greater linkage between work and family concerns in India than in Canada. Schwalb et al (1992) found that Japanese employees reported being motivated by the task itself, self-improvement, and financial reward, in contrast with a greater US emphasis upon affiliation, social concern, and recognition. Holt & Keats (1992) compared Anglo, Chinese, Lebanese, and Aboriginal Australians.…”
Section: Work Motivationmentioning
confidence: 88%
“…For example, empathy (e.g., the ability to read other people's emotions) and social deftness (e.g., knowing how to respond to other people's emotions in an appropriate manner) are culturally influenced. In relation to the self-efficacy and/or motivation aspect of emotional intelligence, a wide body of management research exists that demonstrates the cultural sensitivity in this area (Aycan et al, 2000;Schwalb, 1992;Super & Sverko, 1995;Yu & Yang, 1994). Indeed, Osteraker's (1999) dynamic triangle of motivation places culture in an influential position for determination of a participant's motivational disposition.…”
Section: Higher Order Skills and Cultural Intelligencementioning
confidence: 99%
“…Although some basic structures of motivation may be universal (Triandis, 1994), the fact that culture has been linked to motivation is well established (e.g. Aycan, 2001;Schwalb, 1992;Super and Sverko, 1995;Yu and Yang, 1994). It is this basic link that makes a cultural understanding of the subject context (i.e.…”
Section: Culture and Motivationmentioning
confidence: 99%